Annual Plan 1971-72 Government of India Planning Commission - Planning Commission (Planning Commission, 1971)
The Annual Plan for 1971-72 presented in this Document has been finalised within the broad framework set out in the Fourth Five Year Plan (1969-74) which was placed before the Parliament in May 1970. 2. Initial steps for the formulation of the Annual Plan 1971-72 were taken by the Planning Commission in the month of August 1970. A modified procedure was followed for the preparation of the Annual Plans both of the States as well as of the Union Territories. Working Groups comprising representatives of the Planning Commission,
Government of India Planning Commission